Confronting the frame: a critical analysis of selected narratives that persist in the Village Museum, Stellenbosch, South Africa, c.2014 – 2024 - Biscombe, Monique Isabel (Stellenbosch : Stellenbosch University, 2026)
Thesis (DPhil)--Stellenbosch University, 2026.